Quantification of plankton-sized microplastics in a productive coastal Arctic marine ecosystem. (November 2020) - Rist, Sinja; Vianello, Alvise; Winding, Mie Hylstofte Sichlau; Nielsen, Torkel Gissel; Almeda, Rodrigo; Torres, Rocío Rodríguez; Vollertsen, Jes
Abstract: Microplastics (MPs) are polluting the Arctic, but our understanding of their abundance, distribution, and sources is limited. This study quantified MPs down to 10 μm in marine waters of the most populated region in Greenland. A new plastic-free pump-filter system was used to collect MPs from surface waters in the fjord Nuup Kangerlua close to Nuuk. Additionally, we took samples by horizontal tows with a bongo net (300 μm mesh-size). The median concentrations were 142 MPs m −3 and 0.12 MPs m −3 in the pump and bongo samples, respectively. The most abundant polymer was polyester across stations and sampling types. Fibers were the dominant shape in the bongo samples, while non-fibrous particles dominated in the pump samples. MP abundance was lower in the fjord and increased close to Nuuk and towards the open ocean, indicating that Nuuk is an important point source for MPs. In both samples, concentrations of MPs increased with decreasing size, illustrating the importance of quantifying the smallest fraction of MPs. Thus, the use of methods allowing for a quantification of the smallest MPs is vital to reduce the underestimation of MP concentrations in the environment. The smallest size fraction is also most available to plankton-feeding marine invertebrates and an important entry point for MPs into marine food webs. At the found concentrations, immediate adverse effects on the pelagic food webs are unlikely. However, growing anthropogenic activities could increase the risk of MPs to affect the sensitive Arctic ecosystem. Graphical abstract: Image 1 Highlights: Microplastics (>10 μm) were quantified in West Greenland with a new pump system. Seawater concentrations were 2–3 orders of magnitude higher than in bongo net tows. Microplastics likely originated from local sources, with Nuuk being a point source. Microplastic abundance increased with decreasing particle size. The dominant particle size is the most available for plankton-feeding invertebrates. Abstract : Sampling of microplastics >10 μm in West Greenland with a new pump system demonstrated the dominance of the smallest size fraction, which is the most likely to enter pelagic marine food webs.